Factors Influencing People's Decision to Save in Sharia Bank (Case Study in Sleman District) - Fathurrahman, Ayif; Ratnasari, Dian Puspita (Universitas Muhammadiyah Makassar, 2024)
This research aims to analyze the determinants that have an influence on savings decisions in regional sharia banks in Sleman Regency. The possibility of a technical sample is the sampling technique in this research. From this technique there were 116 respondents. This research data is primary data with multiple linear regression methods. Research finds that the religiosity variable has no influence on people's decisions to save in Islamic banks. Meanwhile, the variables of trust, level of results and knowledge have a significant positive influence on the decision to save. Meanwhile, simultaneously all the research variables that influence the decision to save at a regional sharia bank in Sleman Regency with a coefficient of 0.630 promise from the results of this research that sharia banks are able to maintain the variables of trust, knowledge and level of profit sharing which are the dominant factors that influence people to save at the k sharia bank.